2019
DOI: 10.1111/jvs.12709
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of terrestrial and epiphytic ferns and lycophytes along an elevational gradient in Southern Brazil

Abstract: Questions What are the drivers that govern fern and lycophyte community composition across different elevation zones in the South Brazilian Atlantic Forest? Does explanatory power of the models increase when we consider substrate‐based life forms separately? Do terrestrial and epiphytic species respond similarly to environmental drivers? Study site Four distinct elevation zones of the Atlantic Rain Forest sensu stricto in northeastern Rio Grande do Sul, Brazil. Method Variation partitioning was used to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The higher species richness of epiphytes at a higher altitude in Honduras is likely the result of increased precipitation and more continuous water supply (McAdam & Brodribb 2012;Nervo et al 2019). Epiphytic species that are sensitive to water availability appeared to favour higher altitudinal sites, with lower-temperature conditions, increased cloud formation and a supply of fine and frequent precipitation compared to low-altitudinal sites (Bhattarai et al 2004;Frahm & Gradstein 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher species richness of epiphytes at a higher altitude in Honduras is likely the result of increased precipitation and more continuous water supply (McAdam & Brodribb 2012;Nervo et al 2019). Epiphytic species that are sensitive to water availability appeared to favour higher altitudinal sites, with lower-temperature conditions, increased cloud formation and a supply of fine and frequent precipitation compared to low-altitudinal sites (Bhattarai et al 2004;Frahm & Gradstein 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, the individual response of particular plant groups has been shown to vary greatly (Grau et al 2007(Grau et al , 2011Wolf et al 2016). For example, epiphytes, which are restricted to life in the canopy, are often separated from the terrestrial soil environment and have been suggested to therefore respond very differently compared to terrestrial plants (Nervo et al 2019); particularly as epiphytes are also highly sensitive to changing climate conditions (Ellis 2013;Ellis & Coppins 2007Hsu et al 2012;Zotz & Bader 2009). Thus, the lack of altitudinal distribution data on terrestrial and epiphytic ferns and lycophytes from Honduras currently prevents us to compare plant distributional responses to predicted changes in future climate to other biodiversity hotspots (Marchese 2015;Myers et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike what has been observed in terrestrial plants, where arbuscular mycorrhizal symbiosis is extremely common, the biological importance of this in plants occupying other niches is less clear. The epiphytic habitat poses different demands to plants compared to the terrestrial habitat and the slow growth rate in lycophytes and ferns (Nervo et al 2019) should affect the relationship with the fungi. For forest epiphytes that naturally grow below the canopy, where there is less light, access to water depends on rainfall and relative humidity, and the availability of inorganic nutrients is influenced by morphological and chemical properties of the bark of the host tree (Reinert 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The elevational range in a region and the macroevolutional history of specific fern groups are essential to the development of the latitudinal diversity pattern of ferns [25,32,37]. Human activities, environmental heterogeneity, soil, and topography also affect fern diversity at different elevations [8,23,34,38,39]. Researchers have argued that geometrical constraints, such as the mid-domain and area effects, might help to explain the hump-shaped patterns [9,22,26,36,40].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have argued that geometrical constraints, such as the mid-domain and area effects, might help to explain the hump-shaped patterns [9,22,26,36,40]. Another cause of diversity patterns is that different fern groups show different latitudinal and elevational diversity patterns [24,35,39,41]. For example, the richness of terrestrial xerophytic ferns often decreases with elevation; whereas, the richness of epiphytic ferns and terrestrial hygrophytic ferns generally increase with elevation [24,41].…”
Section: Introductionmentioning
confidence: 99%